Využití dotačních prostředků pro rozvoj vybrané oblasti - Horáková, Tereza (Vysoké učení technické v Brně. Fakulta stavební)
Tématem této bakalářské práce je financování projektu ve Starém Městě za pomocí dotačních prostředků poskytnutých z Evropských dotací z Integrovaného regionálního operačního programu. Jsou zde popsány související body jako je financování, evropské dotační fondy, regionální politika a definování vlivu této investice na rozvoj území.

This bachelor thesis deals with the financing of the project in the city of Staré Město with the help of grant funds provided from the European subsidies from the Integrated Regional Operational Program. It describes related points such as funding, European subsidy funds, regional policy and defining the impact of this investment on territorial development.
Use of the subsidies for development of selected area
Keywords: investiční rozhodování; investice; město; dotační programy; dotace EU; financování; rozvoj území; veřejné investice; Investment decision-making; city; subsidy resources; investment financing; territorial development; public investment; EU structural policy